WATER SHORTAGE IN AFRICA - Farmonova , Maftuna; Malikova , Nasima (Innovative Development in Educational Activities, 2023)
The problem of water scarcity has cast a shadow over the wellbeing of humans. According to estimates, in 2016, nearly 4 billion people – equivalent to two-thirds of the global population – experience severe water scarcity for a prolonged period of time. If the situation doesn’t improve, 700 million people worldwide could be displaced by intense water scarcity by 2030. Water scarcity remains a critical challenge in many regions across Africa, posing significant threats to both human well-being and environmental sustainability. Africa, in particular, is facing severe water scarcity and the situation is worsening day by day. Resolute and substantial action is needed to address the issue. In this article we will consider the causes and consequences of the problem of shortage of water. This article embarks on a thorough examination of the intricate tapestry of water scarcity in Africa current challenges, and potential pathways to sustainable solutions.